CONTROL ESTADÍSTICO DE PROCESOS EN LA FABRICACIÓN DEL JABÓN DE ACEITE DE GIRASOL OZONIZADO. - Rodríguez Zuñiga, Wendy; González Pita, Mayra C.; Fernández Ruiz, Rosabel; Fernández Cerver, Mirna (Revista CENIC Ciencias Quimicas, 2025)
Introduction: ozonated sunflower oil soap has germicidal and skin-revitalizing properties, being used in medical, podiatric, dermatological, cosmetological treatments or simply as a commonly used soap to keep skin healthy and hydrated. The objective of the work was to apply statistical process control in the manufacture of ozonated sunflower oil soap. Materials and Methods: the quality analysis was carried out on the soap shavings and on batches of topical OLEOZON®, used in the production of soap. Industrial batches of soap, packaged in cardboard boxes and stored at room temperature and at 5 ± 3 ºC, had their organoleptic properties, content of fatty acids insoluble in alcohol, losses due to drying, wear due to softening, foaming power, index of cracking and caustic free alkalinity, for 12 months. From batches produced between january 2022 and august 2023, control charts were obtained, process capacity indices were determined for the content of fatty acids, insoluble in alcohol, and drying losses. Results and Discussion: the batches of topical OLEOZON® and soap shavings satisfactorily met quality specifications. The soap maintained its organoleptic properties, without the presence of cracks or fissures. The parameters remained within the quality specifications, except for drying losses and foaming power, so they were stable for one month, in both storage conditions. Conclusions: the production process of ozonated sunflower oil soap is under statistical control, complying with quality specifications for alcohol insolubles, fatty acids and drying losses. The processes were capable of insoluble in alcohol, fatty acids and drying losses, with high Cp and Cpk indices.